2008
DOI: 10.4161/cbt.7.8.6696
|View full text |Cite
|
Sign up to set email alerts
|

Trophinin: What embryo implantation teaches us about human cancer.

Abstract: Aggressive behaviors of trophoblasts during embryo implantation resemble to those of malignant tumor cells. As much as 20-40% of all epithelial cancers in humans express human chorionic gonadotrophin (hCG), a marker for trophoblast. Therefore it is not surprising if some mechanisms are shared by cancer and trophoblast. However, the molecular basis of human embryo implantation is not well understood due to difficulties in studying the process in humans. Mechanisms of human embryo implantation are unique, as are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 52 publications
0
12
1
Order By: Relevance
“…In testicular and colon cancer, trophinin expression is associated with invasive activity of tumor cells. [23][24][25] In the invasive trophoblast, interactions of trophinin with cytoplasmic signaling molecules may differ from those in silent trophectoderm cells described our previous study in reference 9, or from those occurring in endometrial epithelial cells described here.…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tcontrasting
confidence: 57%
“…In testicular and colon cancer, trophinin expression is associated with invasive activity of tumor cells. [23][24][25] In the invasive trophoblast, interactions of trophinin with cytoplasmic signaling molecules may differ from those in silent trophectoderm cells described our previous study in reference 9, or from those occurring in endometrial epithelial cells described here.…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tcontrasting
confidence: 57%
“…Novinec et al [34] also described another protein with sequence similarity to the Tg1 domain, trophinin. This membrane protein has been shown to mediate the adhesion of homophilic cells [51]. We think the Tg1 region may mediate the binding of thyroglobulin to the thyrocyte apical membrane.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have suggested that the expression of TROPHININ was frequently observed in patients bearing malignant or metastatic tumors, including testicular germ tumor and adenocarcinomas of colon and lung [12]. To investigate whether KIAA1114 shows analogous pattern of expression in cancer, epithelial cell lines of various tissue origin were subjected to flow cytometric analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Previous reports have suggested that the presence of numerous translational initiation sites in trophinin mRNA and utilization of different alternative splicing could generate three major types of proteins – KIAA1114, TROPHININ, and MAGPHININs [10, 11]. Although a number of studies have been performed on dissecting the physiological role and function of TROPHININ in embryo implantation and cancer progression [12], only few studies have been conducted on a full-length protein encoded by the trophinin gene known as KIAA1114, whose cDNA coding sequence was initially identified from human brain [13]. Despite the reported expression of KIAA1114 at the transcriptional level, physiological evidence for the existence of KIAA1114 at the protein level has never been reported to date, making it a “hypothetical” protein for more than a decade.…”
Section: Introductionmentioning
confidence: 99%